Recycling of Industrial Waste Water for the Generation of Electricity By Regulating the Flow Control Sensor using IoT - Kaviyaraj. R; Karthika M S; Jeni Narayanan L.A; Saleekha . (Institute of Advanced Engineering and Science, 2018)
The paper focuses on generating the renewable energy source from industrial waste water effluents. Utilizing the industrial waste water in order to generate electricity, a flow control sensor has been installed at the outlet of the tunnel which passes the waste water to the turbine. As per the need, the generation of electricity varies with respect to the flow through the use of flow control sensor. The generated electricity is then used for powering the street lights, gardening and run-way paths, during night time. The flow control sensor when integrated using IoT and cloud storage facilitates efficiency and scalability thereby providing massive utilization of energy usage.